VD_FINDINFO MP / 2010 / 27 vom 25. November 2010 - VD Tribunal cantonal (2010)
PROTECTION DE LA PERSONNALITÉ, REGISTRE DES POURSUITES, ACTION EN CONSTATATION | 28 al. 2 CC, 28 CC, 28c al. 1 CC, 28c CC, 101 CPC, 8a LP